A review of the genus Lipotactes Brunner v. W., 1898 (Orthoptera, Tettigoniidae, Lipotactinae) from China - Shi, Fu-Ming; Li, Rui-Lian (Zootaxa, 2009)
In the current paper, a key to the species of Lipotactes Brunner v. W. occuring in China is given. Two species are described as new, L. laminus sp. nov. and L. truncatus sp. nov. The material, on which the study is based including the type specimens is deposited in the Museum of Hebei University.